1995
DOI: 10.1071/ch9951125
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin and Termethylated Cyclodextrin Complexation of Aromatic Carboxylic Acids and Their Conjugate Bases in Aqueous Solution: the Effect of Size, Hydrophobicity and Charge

Abstract: For a-cyclodextrin (~c D ) , the complexation constants (K) for the formation of binary host-guest complexes (HA.acD) are 750f60, 1070f60, 2 7 f 3 and 1 7 f 4 dm3 mol-I when the guests (HA) are benzoic, 4-methylbenzoic and (R)and (S)-2-phenylpropanoic acids, respectively, as determined by potentiometric titration in aqueous solution at 298.2 K and I = 0.10 mol dm-3 (KCl). For the analogous hexakis(2,3,6-tri-0-methyl)-a-cyclodextrin complexes (HA.TM~cD), K = l58Of 150, 289Of 130, 220f 10 and 2O7f 8 dm3 mol-l, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The crystallographic result gives better insight into the b-CD-BA inclusion complex than do the others previously reported. [10][11][12][13][14] For example, the results obtained in solution by NMR, 10 by potentiometric titration; 11 in the gas phase by FAB mass spectrometry, 12 by theoretical calculations 13 have shown that the host-guest stoichiometry is 1:1, the BA aromatic ring is parallel to the CD molecular axis and the COOH group points toward the narrower rim of the cone. In the solid state, thermal analyses and X-ray powder diffraction have revealed significant interactions between b-CD and BA in both physical and kneaded mixtures with a 1:1 host-guest molar ratio.…”
mentioning
confidence: 97%
“…The crystallographic result gives better insight into the b-CD-BA inclusion complex than do the others previously reported. [10][11][12][13][14] For example, the results obtained in solution by NMR, 10 by potentiometric titration; 11 in the gas phase by FAB mass spectrometry, 12 by theoretical calculations 13 have shown that the host-guest stoichiometry is 1:1, the BA aromatic ring is parallel to the CD molecular axis and the COOH group points toward the narrower rim of the cone. In the solid state, thermal analyses and X-ray powder diffraction have revealed significant interactions between b-CD and BA in both physical and kneaded mixtures with a 1:1 host-guest molar ratio.…”
mentioning
confidence: 97%
“…The thermodynamic characteristics of the formation of complexes of inclusion of cyclodextrins with BA and its derivatives in water and the structure of the resulting complexes in the crystalline state are presented in numerous literature sources [ 10 , 11 , 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Most of them indicate the formation of complexes with a 1:1 stoichiometric ratio due to the predominance of van der Waals interactions and H-binding between guest molecules and CDs.…”
Section: Discussionmentioning
confidence: 99%